Remarks at the Western and Central Africa Regional Media Roundtable - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass spoke about the Coronavirus (COVID-19) pandemic that has taken a toll on African lives, economies, and livelihoods. The World Bank intends to invest and mobilize about $150 billion over the next five years in Africa to support the continent’s recovery from the pandemic and its long-term development. He urged countries that expect to have excess vaccine supplies to release their excess as soon as possible to developing countries that have delivery programs in place. He emphasized the need for greater transparency in contracts between governments, pharmaceutical companies, and organizations that are involved in vaccine production and delivery so that financing can be directed effectively, and countries can plan for receipt and deployment. The World Bank yesterday launched a comprehensive online portal that provides easy access to information about their projects, including individual country-financing operations. He spoke about comprehensive debt solutions which will involve at least four elements: debt suspension, debt reduction, debt resolution, and debt transparency. He stated that without private creditors fully onboard, the Common Framework will not deliver a sustainable solution for Chad, Ethiopia, or Zambia. As countries work to recover, tackling climate change will be key for the region. The Bank is also working to address fragility, conflict, and violence. He concluded that while we know that the road to recovery will be long, countries in the region have applied lessons from previous crisis such as the West Africa Ebola outbreak in 2014, and many countries have strengthened their social safety nets to help protect the poor that have been most affected by the crisis, and to move faster on key reforms and investments that will be crucial for long-term development.